Plasma progesterone profiles in relation to postpartum ovarian activity in the swamp buffalo - M. R., Jainudeen; Tan, H. S.; Bongso, T. A. (1981)
Ovarian activity in 38 suckled swamp buffaoes (Bubalus bubalis) was monitored by rectal palpation, oestrus detection and plasma progesterone radio-immunoassay from calving to approximately 150 days postpartum. Three categories of ovarian activity were diagnosed clinically : A corpus luteum (CL) with detected oestrus (21%), a CL with nondetected oestrus (42%) and no CL with non-detected oestrus or anestrus (37%). Plasma progesterone levels confirmed the clinical diagnosis of the presence or absence of a palpable CL except that progesterone levels were low (<0.2ng/ml) when a CL was palpable in 67% of the cows between Day 30 and 60 postpartum. During the oestrous cycle, plasma progesterone levels were low (0.24±0.12ng/ml) during oestrus (Day 0), rose to detectable levels (0.42±0.21ng/ml) by Day 6, reached a peak concentration (1.51±0.35ng/ml) on Day 15 and then declined to basal levels (0.2ng/ml) on Day 22. A synthetic prostaglandin F₂α analog induced oestrus and ovulation in cycling buffaloes but neither a synthetic gonadotropin releasing hormone nor a progesterone releasing intravaginal device was effective in initiating ovarian activity in anestrous buffaloes.